2016
DOI: 10.7717/peerj.2659
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane postconditioning attenuates cardiomyocyte hypoxia/reoxygenation injury via restoring mitochondrial morphology

Abstract: BackgroundAnesthetic postconditioning is a cellular protective approach whereby exposure to a volatile anesthetic renders a tissue more resistant to subsequent ischemic/reperfusion event. Sevoflurane postconditioning (SPostC) has been shown to exert cardioprotection against ischemia/reperfusion injury, but the underlying mechanism is unclear. We hypothesized that SPostC protects cardiomyocytes against hypoxia/reoxygenation (H/R) injury by maintaining/restoring mitochondrial morphological integrity, a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…It is confirmed that I/R down‐regulates the expression of mitochondrial fusion proteins including Mfn1, Mfn2, and Opa1, disrupts mitochondrial fusion and increases cardiomyocyte apoptosis (Cellier et al, ; Dong, Chen, et al, ; Yang et al, ; Yu et al, , ; Zhao et al, ). Multiple lines of evidence suggest that inhibition of endogenous fusion proteins enhances I/R‐induced cardiomyocyte apoptosis, and up‐regulation of fusion proteins suppresses I/R‐induced cardiomyocyte apoptosis.…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 87%
See 2 more Smart Citations
“…It is confirmed that I/R down‐regulates the expression of mitochondrial fusion proteins including Mfn1, Mfn2, and Opa1, disrupts mitochondrial fusion and increases cardiomyocyte apoptosis (Cellier et al, ; Dong, Chen, et al, ; Yang et al, ; Yu et al, , ; Zhao et al, ). Multiple lines of evidence suggest that inhibition of endogenous fusion proteins enhances I/R‐induced cardiomyocyte apoptosis, and up‐regulation of fusion proteins suppresses I/R‐induced cardiomyocyte apoptosis.…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 87%
“…Under I/R conditions, mitochondrial fission plays a key role in regulating cardiomyocyte apoptosis. Mitochondrial fission proteins including Drp1, Fis1, MFF, Mtfr1 as well MTP18 are up‐regulated in cardiomyocytes exposed to I/R, followed by the increase of mitochondrial fission and cell apoptosis (Long et al, ; Wang et al, ; Wang, Gan, et al, ; Yang et al, ; Yu et al, , ; Zaja et al, ). And I/R also stimulates the translocation of Drp1 from the cytosol to mitochondria (Cellier et al, ; Din et al, ; Ikeda et al, ).…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 99%
See 1 more Smart Citation
“…31,34 A previous study showed that impairment of HIF-1 can lead to a surge in ROS generation. 31,34 A previous study showed that impairment of HIF-1 can lead to a surge in ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our latest studies have shown that mitochondria are the terminal operating apparatuses of S-post mediated cardioprotection (Yu et al, 2016a, 2016b). Mitochondria are major sources of ROS during myocardial I/R.…”
Section: Discussionmentioning
confidence: 99%